Peripheral artery disease in patient with end-stage renal disease on regular hemodialysis: a case report - Chandra, I. Made A.; Aryana, I. Made L. (International Journal of Research in Medical Sciences, 2022)
Patients with end-stage renal disease (ESRD) had a higher risk of developing cardiovascular disease, including peripheral artery disease (PAD). The presence of PAD in hemodialysis patients leads to an increase in the incidence of amputation and mortality. However, early diagnosis of PAD in hemodialysis patients is still challenging. Clinical manifestation of PAD in ESRD patients is often atypical manifestations and present in severe manifestations. We reported a case of PAD in the right leg of a 54-year-old woman with end-stage renal disease (ESRD) on regular hemodialysis with comorbid diabetes mellitus and hypertension. Ankle-brachial index (ABI) of the right leg was 0.82 and the result of echo-Doppler supported the presence of PAD in the right distal femoral artery. Then, the patient was treated with antiplatelet therapy, cilostazol, and other medication to control comorbidities. The pain was partly relieved after treatment and the patient was referred to a tertiary hospital for further diagnosis and management. Endocrine and biochemical abnormalities lead to a higher prevalence of PAD in ESRD patients on routine hemodialysis. The non-invasive approach on PAD in ESRD patients has an advantage in improving patients’ outcomes if the diagnosis is established in the earlier stage.